Rewriting the hybrid: sinification and identity negotiations under Hong Kong's national security law regime - Hansen, Adam (Nanyang Technological University, 2025)
This study investigates how state authorities and members of the Hong Kong public negotiate between a distinct Hong Kong identity and a Chinese identity under the current National Security Law regime, and the implications it has for the city’s autonomy. Employing a mixed-methods research design, three critical spaces for identity negotiations are analyzed during the timeframe of June 2020 through March 2025: legal, educational, and transnational. Drawing on Bhabha’s concept of hybridity and Gramsci’s cultural hegemony, it argues that Beijing has increased its presence in local Hong Kong institutions through coercive and consensus-based promotion of a China-centric identity. In the legal space, trials are used to delegitimize Hongkonger values tied to civil liberties, while patriotic education rewrites history, morality and identity to align Hong Kong people with the Mainland. Through online and diasporic activities, the Hongkonger identity continues to be expressed, drawing on both anti-Chinese sentiments and addressing its colonial legacy. However, with limited counter-hegemonic ability inside the city, the Hong Kong hybrid identity is increasingly becoming sinified, reducing the strength of values behind protests of both 2014 and 2019, tightening Beijing’s grip of the city.